Characteristics of somatometric indicators of children 5-6 years old with different postural types as a development precondition of the concept on prophylactic and correction of functional disorders of the support-motional apparatus during the process of physical rehabilitation - Kashuba, Vitaliy; Nosova, Nataliya; Bondar, Olena (Journal of Education, Health and Sport, 2017)
Actuality. Insufficient physical activity in children is one of the reasons for the deterioration of children's health, the decreasing of vitality. The prevalence of functional disorders is more than 70% by the time a child enters school. The functional disorders of the musculoskeletal system in children 5-6 years old are leading according to the scientific social data. The research objective: to study the indicators of child’s physical development with different postural types in senior preschool age, as a precondition for the development of the concept on prevention and correction of functional disorders of the musculoskeletal system of children 5-6 years old during the physical rehabilitation process. The research results. It was established in the research that 87.5% of children in senior preschool age have postural disorders with an increase or decrease in the physiological curves of the spinal column. The results of our research show that the somatometric indicators of children without postural disorders differ significantly from those of children with disorders in biogeometric postural profile.Conclusions. It was established in the research that 87.5% of children in senior preschool age have postural disorders with an increase or decrease in the physiological curves of the spinal column. Prospects for further research are promoted by development and introduction of concepts on correction and prevention of functional disorders in the support-motional apparatus of children in preschool age during the process of physical rehabilitation.